(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: This study explores research attitudes in Lahore-based BS Nursing and Medical students, recognizing research as a significant scientific process that addresses knowledge gaps and enhances healthcare practice. Through analyzing these groups of students’ attitudes towards research implementation, the study seeks to encourage research participation in healthcare education. Objective: To compare the attitudes of BS Nursing and Medical students in executing research tasks and their attitudes toward research involvement. Methods: Comparative research design was selected to conduct this study. Modified Attitude towards Research scale used as research tool. 128 students from Rashid Latif Khan University Lahore, Pakistan which consist of 32 BS Nursing and 96 Medical students were included in research study through online Google doc survey. Results: The study included 32 BS Nursing and 96 Medical students, the study depicts that BS Nursing (M=97.59±12.14) and medical students (M=98.68±13.81) had comparable attitudes towards research implementation (mean difference=1.09, p=0.517). A poor correlation (r=-0.119) revealed no significant intergroup difference. Conclusion: The research attitude was found to be no different between nursing and medical students and both groups were found to have similar levels of participation and perception. The findings from the data reveal that neither group is significantly better in research implementation. Recommendation: The future multi-center studies with various illustrations should discover relative aspects and longitudinal strategies to reinforce generalizability and perceptions into research dispositions.